Acidified Ethanol Improves Extraction Yield while Modulating Antioxidant Activity in Butterfly Pea Extracts - Nellen Fadillah Permata Rachman; Selly Harnesa Putri; Anis Yohana Chaerunnisaa; Desy Nurliasari (METANA, 2026)
Butterfly pea (Clitoria ternatea L.) flower is rich in bioactive compounds, particularly flavonoids and anthocyanins, which contribute to its antioxidant properties. This study evaluated the effect of ethanol and ethanol-citric acid extraction on extract yield, phytochemical composition, and antioxidant activity. Results showed that ethanol-citric acid extraction increased the yield from 30.14% to 44.58% but reduced the extract pH from 4.58 to 2.25. Phytochemical screening confirmed the presence of flavonoids, saponins, tannins, and triterpenoids in both extracts. Antioxidant activity analysis using DPPH revealed that ethanol extraction exhibited stronger antioxidant activity (IC50 = 98.74 ppm) than ethanol-citric acid extraction (IC50 = 146.46 ppm). These findings suggest that citric acid enhances extraction yield but may reduce antioxidant stability. Further research is needed to assess the impact of extraction conditions on the functional properties of butterfly pea flower extract